The walking dead. Vol. 14, No way out - Kirkman, Robert (Kirkman, Robert. Walking dead., 2011)
Rick and his group of survivors discover that life within the community they have found in Washington, DC, is not as safe as they hoped, with their new friends not exactly who they appear to be, and danger hiding within the walls.